Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1097/md.0000000000030980
|View full text |Cite
|
Sign up to set email alerts
|

The baseline and repeated measurements of DBP to assess in-hospital mortality risk among critically ill patients with acute myocardial infarction: A retrospective cohort study

Abstract: Changes in diastolic blood pressure (DBP) are common in patients with acute myocardial infarction (AMI). The relationship between the dynamic change of DBP and in-hospital mortality among patients with AMI remains unclear. This study aimed to explore the importance of DBP during disease development among patients with AMI. We performed a retrospective cohort study involving patients from the Medical Information Mart for Intensive Care III database, which included > 40,000 patients admitted to the intensive car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Torabi et al [15] also examined patients in the ESI category three and found that SBP and ASI values were better in determining mortality than SI and MSI. In another study, a non-linear correlation between baseline DBP and in-hospital mortality in patients with acute myocardial infarction was found, and a decrease in DBP within the first three days in patients who had a mortal course [16]. Lee et al [17] determined that the SpO 2 /RR ratio is an independent prognostic factor for 28-day mortality in patients with sepsis or septic shock.…”
Section: Discussionmentioning
confidence: 96%
“…Torabi et al [15] also examined patients in the ESI category three and found that SBP and ASI values were better in determining mortality than SI and MSI. In another study, a non-linear correlation between baseline DBP and in-hospital mortality in patients with acute myocardial infarction was found, and a decrease in DBP within the first three days in patients who had a mortal course [16]. Lee et al [17] determined that the SpO 2 /RR ratio is an independent prognostic factor for 28-day mortality in patients with sepsis or septic shock.…”
Section: Discussionmentioning
confidence: 96%